An Analysis of Labor Force Participation, Employment, and Unemployment Rates Among the Elderly Population - Korkutan, Mümtaz; Uzun, Hasan (Fırat University, 2025)
This study examines the labor force participation, employment and unemployment rates of the elderly population in Turkey between 2019 and 2024. Based on TurkStat data, the study reveals that the proportion of the elderly population in the total population increased from 9.1% to 10.2% and demographic aging continues. In the gender distribution of the elderly population, the proportion of women (55.5%-55.8%) is higher than men (44.2%-44.5%), which can be attributed to women's longer life expectancy. The trend in the labor force participation rate of older people was 12.5% in 2019, fell to 10% in 2021, and rose to 12.2% in 2023. These fluctuations can be explained by the effects of the COVID-19 pandemic and changes in economic conditions. By gender, the labor force participation rate of the male older population (16.8-20.9%) is significantly higher than that of the female older population (4.6-6.1%). Employment rates show a similar trend, being higher for men (16.2%-20.2%) than for women (4.6-6%). The unemployment rate fluctuated between 2.7% and 3.1% between 2019 and 2023, being higher for men (3.1-3.9%) than for women (0.8-1.7%). These findings reveal that the position of the elderly population in the labor market shows gender-based differences and that more inclusive approaches are needed in employment policies for the aging population. The study analyzes the position of the elderly population in the labor force and offers inclusive policy recommendations for the future.

Bu çalışma, Türkiye’de 2019-2024 yılları arasında yaşlı nüfusun iş gücüne katılım, istihdam ve işsizlik oranlarını incelemektedir. TÜİK verilerine dayanan araştırma bulgularına göre, yaşlı nüfusun toplam nüfus içindeki oranı %9,1’den %10,2’ye yükselmiş olup, bu durum demografik yaşlanma sürecinin devam ettiğini göstermektedir. Yaşlı nüfusun cinsiyet dağılımında kadınların oranı (%55,5-55,8) erkeklerin oranından (%44,2-44,5) daha yüksektir. Bu farklılık, kadınların ortalama yaşam süresinin erkeklere kıyasla daha uzun olmasından kaynaklanmaktadır. Yaşlı nüfusun iş gücüne katılım oranı 2019 yılında %12,5 iken 2021’de %10’a gerilemiş, 2023 yılında ise yeniden %12,2’ye yükselmiştir. Bu dalgalanmalar, COVID-19 pandemisinin etkileri ve ekonomik koşullarda yaşanan değişimlerle ilişkilendirilebilir. Cinsiyet bazında incelendiğinde, yaşlı erkek nüfusun iş gücüne katılım oranı (%16,8-20,9) yaşlı kadınlara (%4,6-6,1) kıyasla belirgin biçimde daha yüksektir. İstihdam oranları da benzer bir eğilim göstermekte olup, erkeklerde (%16,2-20,2) kadınlara (%4,6-6) göre daha yüksektir. İşsizlik oranı ise 2019-2023 yılları arasında %2,7 ile %3,1 arasında değişmiş; erkeklerde (%3,1-3,9) kadınlara (%0,8-1,7) göre daha yüksek seyretmiştir. Elde edilen bulgular, yaşlı nüfusun iş gücü piyasasındaki konumunun belirgin cinsiyet temelli farklılıklar gösterdiğini ortaya koymaktadır. Bu durum, yaşlanan nüfusa yönelik istihdam politikalarında toplumsal cinsiyet eşitliğini gözeten, kapsayıcı ve sürdürülebilir yaklaşımların geliştirilmesi gerekliliğine işaret etmektedir. Çalışma, yaşlı nüfusun iş gücündeki konumunu analiz ederek, geleceğe yönelik sosyal politika ve istihdam stratejilerine katkı sağlayacak öneriler sunmaktadır.
YAŞLI NÜFUSUN İŞ GÜCÜNE KATILIM, İSTİHDAM VE İŞSİZLİK ORANLARI ÜZERİNE BİR İNCELEME
Keywords: Employment Equity and Diversity; İstihdam Eşitliği ve Çeşitliliği